The Use of Initial Ergonomic Risk Assessment Tools to Identify Work-Related Musculoskeletal Disorders Among Waterbase Operators in Adhesive Manufacturing Company - Yusriman, Eiman Munirah; Amir Haziq Abdul Razak (Progress in Engineering Application and Technology, 2025)
Work-related Musculoskeletal Disorders (WMSDs) are prevalent among workers in industries involving manual handling, repetitive tasks, and poor posture, contributing to both health issues and decreased productivity. This study focuses on ergonomic risks at the adhesive manufacturing company, a manufacturer in the adhesive and sealant located in Industrial State of Senawang, Negeri Sembilan. The research examines ergonomic challenges, identified that the Waterbase production area, where operators engage in manual lifting and material handling that expose them to musculoskeletal disorders are more likely in high risk. Using a combination of ergonomic risk assessment tools from the Department of Occupational Safety and Health (DOSH) Guidelines, including the Initial Ergonomic Risk Assessment (ERA). This study inferred that of all the critical tasks that has been observe showed the majority of the assessment required advanced ERA. The research aims to recommended effective corrective measures and preventive strategies to improve workplace ergonomics, reduce physical strain, and enhance overall productivity by recommending risk control to mitigate the risk.